Trapping and Thrombectomy of Giant Thrombosed Vertebral Artery Aneurysm via Bilateral Subocciptal Approach – Technical Note - Gurung, Pritam; Kuga, Yoshihiro; Kodama, Yuji; Taomoto, Katsushi; Ohnishi, Hideyuki (Eastern Green Neurosurgery, 2020)
Background: Giant aneurysms arising from the vertebral artery (VA) are rare; they represent 4% to 6% of all intracranial giant aneurysm. The natural history of thrombosed aneurysms is extremely poor. Most such lesions progressively enlarge and result in irreversible progression of neurological deficits and fatal sequelae through resultant compression of the brainstem. We present the clinical experience of giant thrombosed vertebral artery aneurysm successfully treated via a bilateral suboccipital approach. A 62 –year-old woman presented with slight dysarthria and ataxia for one year. Neurological examination showed right lateral gaze nystagmus, bilateral absent corneal reflex, absent gag reflex, bilateral dysdiadochokinesia, poor right finger nose test, and slightly poor tandem gait. MRI showed a 27 mm giant thrombosed left VA aneurysm with brain stem compression. We performed trapping of the aneurysm and thrombectomy through a bilateral suboccipital approach. First, the distal portion was clipped from the left side. Next, the proximal portion was approached from the right side. Thrombectomy was performed and after shrinkage of the aneurysm, the clips were applied involving some part of the aneurysm just distal to PICA.Conclusion: The optimum treatment for aneurysm of this type is thought to be complete obliteration of the parent artery with trapping and thrombectomy to decompress the brainstem. Sometimes if PICA could not be preserved Occipital artery (OA)-PICA bypass should be considered.